2022
DOI: 10.3390/molecules27082546
|View full text |Cite
|
Sign up to set email alerts
|

GSH Protects the Escherichia coli Cells from High Concentrations of Thymoquinone

Abstract: The aim of the present study was to evaluate the potential protective effect of glutathione (GSH) on Escherichia coli cells grown in a high concentration of thymoquinone (TQ). This quinone, as the main active compound of Nigella sativa seed oil, exhibits a wide range of biological activities. At low concentrations, it acts as an antioxidant, and at high concentrations, an antimicrobial agent. Therefore, any interactions between thymoquinone and glutathione are crucial for cellular defense against oxidative str… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 31 publications
1
2
0
Order By: Relevance
“…In particular, 14 of the genes upregulated in KO mice belong to the pathway of glutathione metabolism (eco00480), and previous studies demonstrated that glutathione metabolism is involved in protection against oxidative stress. 42 , 43 In addition, Sakamoto et al reported mprA to be involved in resistance to oxidative stress, together with the activity of gshA (glutathione synthase), which is also upregulated in our populations 40 . Additionally, our metatranscriptomic data confirm the findings of Tawk et al, suggesting a role for vitamin B6 metabolism.…”
Section: Discussionsupporting
confidence: 50%
“…In particular, 14 of the genes upregulated in KO mice belong to the pathway of glutathione metabolism (eco00480), and previous studies demonstrated that glutathione metabolism is involved in protection against oxidative stress. 42 , 43 In addition, Sakamoto et al reported mprA to be involved in resistance to oxidative stress, together with the activity of gshA (glutathione synthase), which is also upregulated in our populations 40 . Additionally, our metatranscriptomic data confirm the findings of Tawk et al, suggesting a role for vitamin B6 metabolism.…”
Section: Discussionsupporting
confidence: 50%
“…KatG (catalase) works in concert with these dismutases as it eliminates hydrogen peroxide produced by these manganese and iron-dependent SODs ( Imlay, 2013 ). GshA is required for the biosynthesis of the antioxidant glutathione and the knockout strain is more sensitive to a range of oxygen radicals ( Łyżeń et al, 2022 ). MutT hydolyzes 8-oxo-dGTP to 8-oxo-dGMP to remove it from the nucleotide pool and prevent its misincorporation into DNA ( Ito et al, 2005 ) RecA is required for homologous recombination and is necessary for double-stranded DNA break repair arising from single and double-strand breaks generated by oxygen radicals ( Horii et al, 1980 ).…”
Section: Resultsmentioning
confidence: 99%
“…Interestingly, this is also confirmed by our metatranscriptomic analysis. In particular, 14 of the genes upregulated in KO mice belong to the pathway of glutathione metabolism (eco00480), and previous studies demonstrated that glutathione metabolism is involved in protection against oxidative stress 42,43 . In addition, Sakamoto et al reported mprA to be involved in resistance to oxidative stress, together with the activity of gshA (glutathione synthase), which is also upregulated in our populations 40 .…”
Section: Discussionmentioning
confidence: 99%